Makārim al-akhlāq : Sharḥ-i aḥwāl u zindagānī-yi Amīr ʿAlī Shīr Navāʾī - Khwāndamīr, Ghiyāth al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Ghiyāth al-Dīn Khwāndamīr (d. after 942/1535-6) is a Persian historian who worked for several Timurid rulers in Herat. After the capture of Herat by the Uzbeks in 912/1507 and their ousting by the Safavids in 916/1510, Khwāndamīr held no further public office there. In 927/1520 he went to Agra where he entered the service of the founder of the Mughal dynasty Bābūr (d. 937/1530) and, following the latter's death, his son Humāyūn (d. 963/1556). He died in India, where he was also laid to rest. Khwāndamīr is especially known for his Ḥabīb al-siyar , a universal history from the beginning of time until the reign of Shāh Ismāʿīl I (d. 930/1524). The present work, written at the beginning of his career, is a monument to the greatness of his first patron, the vizier Mīr ʿAlī Shīr Nawāʾī (d. 906/1501). Khwāndamīr's personal involvement in many of the events that it describes lends this work its special interest.